Impaired Intestinal Permeability Contributes to Ongoing Bowel Symptoms in Patients With Inflammatory Bowel Disease and Mucosal Healing - Chang, Jeff; Leong, Rupert W.; Wasinger, Valerie C.; Ip, Matthew; Yang, Michael; Phan, Tri Giang (Gastroenterology (New York, N.Y. 1943), 2017)
Many patients with inflammatory bowel diseases (IBD) have ongoing bowel symptoms of diarrhea or abdominal pain despite mucosal healing. We investigated whether impaired intestinal permeability contributes to these symptoms. We performed a prospective study of intestinal permeability, measured by endoscopic confocal laser endomicroscopy in 110 consecutive subjects (31 with ulcerative colitis [UC], 57 with Crohn’s disease [CD], and 22 healthy individuals [controls]) in Sydney, Australia from May 2009 and September 2015. Symptomatic CD was defined by a CD Activity Index score of 150 or more and symptomatic UC by a partial Mayo score of 2 or more. Mucosal healing was defined as CD Endoscopic Index of Severity of 0 in CD or Mayo endoscopic sub-score of 0–1 for patients with UC. Intestinal permeability was quantified by the Confocal Leak Score (CLS; range: 0=no impaired permeability to 100=complete loss of barrier function). The primary endpoint was intestinal permeability in patients with symptomatic IBD in mucosal healing vs patients with asymptomatic IBD in mucosal healing. We determined the sensitivity and specificity of CLS in determining symptoms based on receiver operating characteristic analysis. Ongoing bowel symptoms were present in 16.3% of patients with IBD and mucosal healing (15.4% of patients with CD, 17.4% with UC). Patients with symptomatic IBD had a significantly higher median CLS (19.0) than patients with asymptomatic IBD (7.3; P < .001) or controls (5.9, P < .001). There were no significant differences between patients with IBD in remission vs controls (P = .261). Median CLS was significantly higher in patients with symptomatic than asymptomatic CD (17.7 vs 8.1; P = .009) and patients with symptomatic than asymptomatic UC (22.2 vs 6.9; P = .021). A CLS of 13.1 or more identified ongoing bowel symptoms in patients with IBD and mucosal healing with 95.2% sensitivity and 97.6% specificity; the receiver operating characteristic area under curve value was 0.88. Based on this cutoff, 36.2% of patients with IBD in mucosal healing have increased intestinal permeability. On regression analysis, every increase in CLS of 1.9 correlated with an additional diarrheal motion per day (P = .008). In a prospective study of intestinal permeability in patients with IBD and mucosal healing, we associated impaired intestinal permeability with ongoing bowel symptoms; increases in permeability correlated with increased severity of diarrhea. Resolution of mucosal permeability beyond mucosal healing might improve outcomes of patients with IDB (ANZCTR.org.au: ACTRN12613001248752).